2021
DOI: 10.1021/acs.biomac.1c01250
|View full text |Cite
|
Sign up to set email alerts
|

Highly Functional Materials Based on Nano-Lignin, Lignin, and Lignin/Silica Hybrid Capped Silver Nanoparticles with Antibacterial Activities

Abstract: Rice husk is one of the most abundant biomass resources in the world, yet it is not effectively used. This study focuses on the sustainably rice-husk-extracted lignin, nano-lignin (n-Lignin), lignin-capped silver nanoparticles (LCSN), n-Lignin-capped silver nanoparticles (n-LCSN), and lignin-capped silica-silver nanoparticles (LCSSN), and using them for antibacterial activities. The final n-Lignin-based products had a sphere-like structure, of which the size varied between 50 and 80 nm. We found that while n-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The antibacterial effect of AgLigNPs demonstrated higher efficiency on Gram-negative bacteria than on Gram-positive bacteria. This tendency, which supports other AgLigNPs studies, 89,95 is attributed to the thicker peptidoglycan wall in Gram-positive bacteria which hinders the penetration of the NPs into the cell.…”
Section: Lignin In Antibacterial Nanoformulationssupporting
confidence: 88%
See 1 more Smart Citation
“…The antibacterial effect of AgLigNPs demonstrated higher efficiency on Gram-negative bacteria than on Gram-positive bacteria. This tendency, which supports other AgLigNPs studies, 89,95 is attributed to the thicker peptidoglycan wall in Gram-positive bacteria which hinders the penetration of the NPs into the cell.…”
Section: Lignin In Antibacterial Nanoformulationssupporting
confidence: 88%
“…94 The resulting spherical shaped NPs, with an average size of 10–50 nm, were able to inhibit the growth of S. aureus and E. coli , and the fungi Aspergillus niger . Following the same procedure, Tran et al 95 prepared AgNPs coated with rice-husk-extracted lignin or nano-lignin (LCSN and n-LCSP). It was found that lignin and nano-lignin were more antibacterial against Gram-positive S. aureus than against Gram-negative E. coli , while the (nano)-lignin-coated AgNPs presented a higher antibacterial effect against the Gram-negative bacterium.…”
Section: Lignin In Antibacterial Nanoformulationsmentioning
confidence: 99%
“…Microstructure images were used to observe the size and morphology of three LNPs, which can impact their impregnation effectiveness due to the anatomical characteristics of wood . All LNPs were clustered and closely stacked (Figure a), possibly due to the linking of EG with lignin . All samples showed a compact size distribution range (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…16−18 The remarkable properties of lignin generated from biomass as a reducing agent or stabilizer for antibacterial chemicals not only help protect the environment, but also increase the value of lignin in future research. 19 However, no reports were found concerning the evaluation of antifungal activities of lignin-based nano hybrid materials prepared from RH. Aspergillus flavus (A. flavus) of peanut and Aspergillus niger (A. niger) of onion are filamentous saprophytic fungi that are found worldwide and frequently infect agricultural goods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of lignin’s hydroxyl groups, carbonyl groups, and double bonds, it can improve the stability of silver-based antibacterial drugs . Furthermore, because lignin is biocompatible, it may be used in medical-pharmaceutical and cosmetic applications such as drug delivery, wound dressing material, antidiabetic activity, cytotoxic activity, and antidiabetic activity in the fight against cancer. The remarkable properties of lignin generated from biomass as a reducing agent or stabilizer for antibacterial chemicals not only help protect the environment, but also increase the value of lignin in future research …”
Section: Introductionmentioning
confidence: 99%